Evidence for the formation of supplementary corpora lutea in the pregnant and pseudopregnant rat - Garside, Deborah A. (1983)
In a series of experiments investigating a possible post-coitum contraceptive, it was observed that the numbers of corpora lutea (CL) of pregnant Sprague-Dawley (CD) rats were greater than in cyclic, unmated control females (p<0.001).